Alexithymia disrupts verbal short-term memory. Issue 3 (3rd April 2021) - Vermeulen, Nicolas
ABSTRACT: While some research has now started to suggest that there are long-term memory (LTM) deficits in alexithymia, short-term memory (STM) in alexithymia remained largely unexplored. This study investigated whether the STM trace for emotion and neutral words might also be disrupted by alexithymia. Forty-four participants were randomly assigned to Study 1 in which the to-be-memorised six-word lists were composed of words belonging to the same valence (i.e. pure lists condition, Study 1), and 44 other participants were randomly assigned to Study 2 in which six-word lists were composed of embedded neutral and emotional words (i.e. mixed lists condition). All the participants completed the Toronto-Alexithymia Scale (TAS-20) and a current mood states scale (PANAS). Results showed that the main effect of alexithymia was observed in the pure lists condition while no alexithymia groups effect emerged in the mixed lists condition. In the pure lists condition only correlation analyses confirmed that alexithymia significantly and negatively correlated with recall accuracy. The results are discussed with regard to the influence of alexithymia on the proposed role of (1) semantic organisation of LTM on STM performance in the pure lists condition and (2) attentional capture by emotional words in the mixed lists condition.